Bio-inspired propulsion of micro-swimmers within a passive cervix filled with couple stress mucus. (June 2020) - Asghar, Zeeshan; Ali, Nasir; Javid, Khurram; Waqas, Muhammad; Dogonchi, Abdul Sattar; Khan, Waqar Azeem
Highlights: A collective locomotion of microorganisms through couple stress fluid is expounded. Cervix is approximated as a passive two-dimensional channel. Spermatozoa is approximated as a complex wavy sheet. Modified Newton-Raphson method is utilized to compute the swimming speed. Abstract: Background and objective: The swimming mechanism of self-propelling organisms has been imitated by biomedical engineers to design the mechanical micro bots. The interaction of these swimmers with surrounding environment is another important aspect. The present swimming problem integrates Taylor sheet model with couple stress fluid model. The thin passage containing micro-swimmers and mucus is approximated as a rigid (passive) two-dimensional channel. The spermatozoa forms a pack quite similar as a complex wavy sheet. Methods: Swimming problem with couple stress cervical liquid (at low Reynolds number) leads to a linear sixth order differential equation. The boundary value problem (BVP) is solved analytically with two unknowns i.e. speed of complex wavy sheet and flow rate of couple stress mucus. After utilizing this solution into equilibrium conditions these unknowns can be computed via Newton-Raphson algorithm. Furthermore, the pairs of numerically calculated organism speed and flow rate are utilized in the expression of power dissipation. Results: This work describes that the speed of micro-swimmers can be enhanced by suitable rheology of the surrounding liquid. The usage of couple stress fluid as compared to Newtonian fluid enhances the energy dissipation and reduces the flow rate. On the other hand complex wavy surface also aids the organisms to swim faster.